Study of Catalytic Activity of Lipase and Lipase-Chitosan Complexes in Dynamics - Savina, Anastasia A.; Abramova, Olga V.; Garnashevich, Lilia S.; Zaitsev, Ilia S.; Voronina, Oksana A.; Tsarkova, Marina S.; Zaitsev, Sergei Yu. (Journal of Research Updates in Polymer Science, 2019)
Pancreatic porcine lipase (PPL) is the unique enzyme in numerous biochemical processes for human and animals. Stability in time is the critical point for many enzymes in relation to their further applications. The effect of chitosan on the activity of PPL during 2 months was investigated. Materials and Methods: Potentiometric method was used to study the catalytic activity of enzymes that based on measuring of the potential an electrode immersed in a triacetin (substrate) solution by titration with 0.01 M NaOH. A laboratory pH-stat with combined pH electrode was used for the measurements of this potential in the presence of PPL or PPL-chitosan complexes. Standard experimental conditions: 40 ºC, pH 7.0. Results: The following PPL activity values (data given in % to the activity of free lipase) vs. time (in 10 min. intervals) were obtained: 100%, 97.4%, 89.9%, 82.9%, 77.9% and 75.9% after 10, 20, 30, 40, 50 and 60 min., respectively. The PPL catalytic activity decreased at about ¼ to ½ of the initial values after 7 or 14 days, 1 or 2 months storage, although there were differences in the decline dynamics. The complex PPL:Chit=50:1 has better stabilizing properties as compared to other complexes; does not strongly inhibit lipase and requires a small amount of carrier (chitosan) for its formation. Conclusions: The complex PPL:Chit=25:1 is less effective as the PPL:Chit=50:1 complex, but both can be applicable in some industrial processes.